Investigation into the prediction accuracy of photocephalometry for skeletal Class III adult female patients treated with two-jaw surgery - Shiu-Shiung Lin; Jui-Pin Lai; Yea-Yin Yen; I-Cherng Chen; An-Hsiung Kuo; I-Chun Yeh (Elsevier, 2012)
Background/purpose: Surgical predictions for skeletal Class III patients have been reported to be the least accurate. Additionally, female patients tend to focus more on improving their facial esthetics. Therefore, this study was aimed at assessing the prediction accuracy of photocephalometry for skeletal Class III adult female patients treated with two-jaw surgery. Materials and methods: A photocephalometric investigation was undertaken to assess the prediction accuracy in a sample of 16 skeletal Class III female patients requiring bimaxillary orthognathic surgery. Tracings of cephalograms and one-to-one predicted photographs were carried out. Selected landmarks were digitized with a user-defined computer program. The prediction accuracy of the facial profile was estimated by evaluating discrepancies in landmark positions between post-surgical cephalograms and pre-planning photographs. Results: Predictions were generally accurate for all horizontal landmark variables and also for the upper lip in the vertical direction. Inaccuracies tended to occur in the vertical direction of the nasal base and lower lip. Mean differences in the predicted nasal base ranged from 1.00-1.06 mm inferior to the actual position. In the lower lip, predictions tended to place the position as more superior, and mean discrepancies were 1.38 mm (for the lower stomion), 2.38 mm (labrale inferius), and 2.06 mm (inferior labial sulcus). Conclusions: In this study predictions were generally accurate in skeletal Class III adult female patients treated with two-jaw surgery. Compared to surgical outcomes, the predictions tended to locate the nasal base more inferior and the lower lip in a more superior position. Prediction inaccuracies and large individual variations found in this report were associated with difficulties in manual photographic manipulation and weak correlations in the vertical direction between the hard tissues and their corresponding soft tissues.